Magnetic resonance imaging before breast cancer surgery: results of an observational multicenter international prospective analysis (MIPA) - Sardanelli, Francesco; Trimboli, Rubina M.; Houssami, Nehmat; Gilbert, Fiona J.; Helbich, Thomas H.; Alvarez Benito, Marina; Balleyguier, Corinne; Bazzocchi, Massimo; Bult, Peter; Calabrese, Massimo; Camps Herrero, Julia; Cartia, Francesco; et al. (SPRINGER, 2022)
Objectives Preoperative breast magnetic resonance imaging (MRI) can inform surgical planning but might cause overtreatment by increasing the mastectomy rate. The Multicenter International Prospective Analysis (MIPA) study investigated this controversial issue. Methods This observational study enrolled women aged 18-80 years with biopsy-proven breast cancer, who underwent MRI in addition to conventional imaging (mammography and/or breast ultrasonography) or conventional imaging alone before surgery as routine practice at 27 centers. Exclusion criteria included planned neoadjuvant therapy, pregnancy, personal history of any cancer, and distant metastases. Results Of 5896 analyzed patients, 2763 (46.9\%) had conventional imaging only (noMRI group), and 3133 (53.1\%) underwent MRI that was performed for diagnosis, screening, or unknown purposes in 692/3133 women (22.1\%), with preoperative intent in 2441/3133 women (77.9\%, MRI group). Patients in the MRI group were younger, had denser breasts, more cancers >= 20 mm, and a higher rate of invasive lobular histology than patients who underwent conventional imaging alone (p < 0.001 for all comparisons). Mastectomy was planned based on conventional imaging in 22.4\% (MRI group) versus 14.4\% (noMRI group) (p < 0.001). The additional planned mastectomy rate in the MRI group was 11.3\%. The overall performed first- plus second-line mastectomy rate was 36.3\% (MRI group) versus 18.0\% (noMRI group) (p < 0.001). In women receiving conserving surgery, MRI group had a significantly lower reoperation rate (8.5\% versus 11.7\%, p < 0.001). Conclusions Clinicians requested breast MRI for women with a higher a priori probability of receiving mastectomy. MRI was associated with 11.3\% more mastectomies, and with 3.2\% fewer reoperations in the breast conservation subgroup.
Keywords: Breast cancer; Magnetic resonance imaging; Mastectomy; Breast-conserving surgery; Reoperation